Moral Work and the Construction of Abortion Networks: Women's Access to Safe Abortion in Lebanon - Zeina Fathallah (Harvard FXB Center for Health and Human Rights, 2019)
This study explores the intersectional effects of criminalization on women's access to safe abortion in Lebanon. Building on 119 original interviews with women who have had an abortion and physicians who offer safe abortion services, the article analyzes women's experiences through two themes: decision making and accessibility to safe abortion services. The article finds that a woman's decision to abort is morally conflicted and largely dependent on her partner: in the case of single women, this turns on whether the partner is willing to marry the woman and assume paternity of the future child, while in the case of married women, this turns on the husband's agreement with the wife's decision. Women use social networks to gain access to information and to clandestine abortion services. Most of the physicians offering abortion services act as moral gatekeepers, often condemning the woman and preserving certain social norms rather than advocating for women's bodily autonomy and free choice. This article argues that the right to safe abortion is a privilege rather than a right in the restrictive Lebanese context, since access to services hinges on a woman's social capital, networks, and ability to negotiate with partners and physicians. Single women from a lower socioeconomic background stand out as the most vulnerable.